(untitled) - Sambrook, Joseph (Cold Spring Harbor, N.Y., 2001)
A major goal of all three editions of Molecular Cloning has been to provide researchers with up-to-date protocols that work reproducibly. Users of the previous editions will recognize many of the organizational features in the experimental sections of this book. Nevertheless, the revision of the text has been extensive and detailed. Ancient protocols have been modernized, while new protocols have been added to reflect the continuing penetration of molecular cloning into almost all areas of biomedical research. Of equal importance has been our desire to explain how and why particular methods work, and with reasoned arguments for choosing between alternative procedures.
Keywords: Molecular cloning,Cloning, Molecular; Laboratory manuals,Laboratory Manuals